Zoon Balanitis: misdiagnosis or missed diagnosis?. (19th November 2019) - Piaserico, S.; Orlando, G.; Linder, M.D.
Abstract : Linked article: C.B. Bunker. J Eur Acad Dermatol Venereol 2020; 34: e116–e117. https://doi.org/10.1111/jdv.16037 .